Analysis of energy security and sustainability in future low carbon scenarios for Brazil - Lima, Fátima (2015)
This study estimated a series of indicators to assess the energy security of supply and global and local environmental impacts under different mitigation scenarios through 2050 in Brazil, designed with the integrated optimisation energy system model MESSAGE-BRAZIL. The assessment of interactions between environmental impacts and energy security dimensions was complemented through the application of life cycle assessment (LCA) methodology. Overall results imply energy security establishes more synergies than trade-offs in increasingly stringent mitigation scenarios, especially patent within the sustainability dimension, which increases energy security and provides additional benefits regarding climate change mitigation and air pollution emissions. It is still necessary to extend analysis to other energy sectors in addition to the power supply sector, to promote a better understanding of repercussions of energy scenario expansion in energy security.